Penerapan Teknik Kolase Untuk Meningkatkan Kemampuan Membaca dan Menulis Permulaan di Kelas I SDK Ende 3 - Maria Kartona Mawa (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
This study aims to improve the initial reading and writing skills in grade 1 students of SDK Ende 3 through collage technique. The research subjects consisted of 29 students. The data were taken by using observation, test and interview techniques. Data were analyzed using simple descriptive statistical techniques to compare the percentage of completeness in each cycle. The results showed an increase in initial reading and writing skills in two cycles after the collage technique was applied to the 1st graders of SDK Ende 3.